EXAMINING THE RELATIONSHIP BETWEEN EMOTIONAL INTELLIGENCE AND CONFLICT MANAGEMENT SKILLS AMONG HEALTH ADMINISTRATION PROFESSIONALS IN KSA - Majab Ayad Shokan Aldhafeeri, Fouad Ali H Hakami, Jaber Farhud T Alsuwayt, Tohary Mohammed Ali M, Ahmed Ali H Hakami, Mohammad Saad Radi Aldafiry, (Chelonian Research Foundation, 2022)
Emotional intelligence (EI) and conflict management skills are crucial competencies for health administration professionals to effectively navigate complex organizational dynamics and interpersonal relationships. This study aims to examine the relationship between emotional intelligence and conflict management skills among health administration professionals in the Kingdom of Saudi Arabia (KSA). A cross-sectional survey was conducted among 400 health administration professionals working in various healthcare organizations across the country. The survey assessed participants' emotional intelligence using the Wong and Law Emotional Intelligence Scale (WLEIS) and their conflict management skills using the Rahim Organizational Conflict Inventory-II (ROCI-II). Descriptive statistics, correlation analysis, and multiple regression were used to analyze the data. The findings revealed a significant positive relationship between emotional intelligence and integrating, compromising, and obliging conflict management styles, while a negative relationship was found with dominating and avoiding styles. The study highlights the importance of developing emotional intelligence among health administration professionals to enhance their conflict management skills and foster a collaborative work environment in healthcare organizations.